An objective short sleep insomnia disorder subtype is associated with reduced brain metabolite concentrations in vivo: a preliminary magnetic resonance spectroscopy assessment - Miller, C; Rae, C; Green, M; Yee, B; Gordon, C; D’Rozario, A; Kyle, S; Espie, C; Grunstein, R; Bartlett, D (Oxford University Press, 2017)
Objectives: To evaluate brain metabolites in objective insomnia subtypes defined from polysomnography (PSG): insomnia with short sleep duration (I-SSD) and insomnia with normal sleep duration (I-NSD); relative to good sleeping controls. Methods: PSG empirically grouped insomnia patients into I-SSD (n=12: mean (SD) total sleep time (TST) = 294.7min (30.5)) or I-NSD (n=19: TST = 394.4min (34.9)). 1H magnetic resonance spectroscopy acquired in the left occipital cortex (LOCC), left prefrontal cortex and anterior cingulate was used to determine levels of creatine, aspartate, glutamate and glutamine (referenced to water). Glutathione, glycerophosphocholine, lactate, myoinositol and N-acetylaspartate measurements were also obtained. Sixteen good sleeping controls were included for comparison. Multivariate analysis of variance was used to evaluate differences in creatine, aspartate, glutamate, and glutamine. Results: Aspartate and glutamine concentrations were reduced in the LOCC in I-SSD compared with I-NSD (both p<.05, d = 0.80-.99). Creatine displayed a non-significant mean reduction in I-SSD compared with I-NSD (p =.05, d = 0.58). Glutamine was reduced in I-SSD compared with controls (p<.05, d = 0.93). There were no differences in metabolites between all (I-SSD plus I-NSD) insomnia patients and controls. In patients with insomnia, LOCC glutamine concentrations were found to be positively correlated with TST (r = 0.43, p<.05) and negatively correlated with wake-time after sleep onset (r = -0.40, p<.05). Conclusions: Results indicate that I-SSD is associated with reduced brain metabolites in the LOCC compared with I-NSD and control concentrations of aspartate, glutamine, and creatine.